Biodiversity patterns of animals in freshwater lakes (Zoological Records and Reviews, 2023)
Freshwater lakes represent biodiversity hotspots that support a disproportionately high fraction of global freshwaterspecies within a limited spatial extent. The inland lakes and reservoirs of the Deccan Plateau, while individually modest in size compared to the African Great Lakes or Himalayan glacial lakes, collectively represent an ecologically significantfreshwater network supporting diverse animal communities including fish, aquatic macroinvertebrates, waterbirds,amphibians, and aquatic reptiles. This study presents a comprehensive assessment of animal biodiversity patternsacross 42 freshwater lakes and reservoirs spanning a gradient of size, trophic state, and human disturbance in AndhraPradesh and Telangana, India, surveyed using standardised fish sampling, macroinvertebrate protocols, waterbird pointcounts, and herpetofauna transects over two annual cycles (2021-2023). A total of 384 animal species from five groupsare documented. Fish (108 species) and waterbirds (148 species) contributed the highest richness. Lake area,macrophyte cover, and trophic state (total phosphorus) are the three strongest predictors of total animal speciesrichness. Hypertrophic urban lakes support fewer than 30% of the species richness of oligotrophic rural reservoirs. Eightfish species are new records for Telangana and Andhra Pradesh. Twelve species are IUCN Threatened. The resultsidentify priority lakes for conservation investment and provide a baseline for long-term freshwater biodiversity monitoring in the Deccan Plateau.
Keywords: aquatic conservation; eutrophication; Andhra Pradesh; Deccan Plateau; trophic state; macroinvertebrates; waterbirds; fish; biodiversity; freshwater lakes